National innovation systems and the achievement of sustainable development goals: Effect of knowledge-based dynamic capability - Xing Li; Ting Wu; Hong-Juan Zhang; De-Yan Yang (Journal of Innovation & Knowledge (JIK), 2023)
The purpose of this paper is to explore the role of knowledge-based dynamic capabilities in national innovation systems in the achievement of sustainable development goals, employing an empirical approach in the context of the unprecedented COVID-19 crisis. Based on data from 130 sample countries, we analyzed the impact of knowledge-based dynamic capabilities on the achievement of sustainable development goals using PLS-SEM. In particular, we considered the differences in the impact of knowledge-based dynamic capabilities on the achievement of sustainable development goals at different stages of economic development. The results show that knowledge-based dynamic capabilities have a positive impact on the achievement of sustainable development goals, while their compositional dimensions have a dual impact, both direct and indirect. In addition, knowledge-based dynamic capabilities have different impacts on the achievement of sustainable development goals at different stages of economic development. This indicates that a country's economic development level will affect the relationship between knowledge-based dynamic capabilities and the achievement of sustainable development goals. However, it also means that there is a more complex relationship between these capabilities and the achievement of the goals. This study offers a new perspective for sustainable development research, adds new insights to the theory of linking knowledge-based dynamic capabilities to the achievement of sustainable development goals, and provides a measurement standard for the impact of those capabilities on the goals.
Keywords: 650; Dynamic capability; Knowledge management; National innovation systems; Sustainable development goals